At low doses ethanol maintains blood-brain barrier (BBB) integrity after hypoxia and reoxygenation: a brain slice study. (1st October 2013) - Peng, Changya; Li, William A; Fu, Paul; Chakraborty, Tia; Hussain, Mohammed; Guthikonda, Murali; Rafols, Jose A; Ding, Yuchuan
Abstract : Post-ischemia ethanol (EtOH) treatments have been shown to exhibit neuroprotective effects in stroke. However, the mechanisms underlying these effects and those on blood-brain barrier (BBB) integrity have yet to be elucidated. In the present study, we determined whether administering differing concentrations of EtOH alter the expressions of BBB integral proteins, including aquaporins-4 and -9 (AQP-4, AQP-9), matrix metallopeptidases-2 and -9 (MMP-2, MMP-9), zonula occludens-1 (ZO-1), and basal lamina (laminin). We employed an organotypic brain slice culture model that utilizes oxygen-glucose deprivation followed by reoxygenation (OGD/R). Brain slices were obtained from 10-day-old Sprague-Dawley rats and divided into the following five groups ( n = 8 subjects per group): (1) control, (2) hypoxia (OGD/R), no EtOH, (3) OGD/R and 10 mM EtOH, (4) OGD/R and 30 mM EtOH, and (5) OGD/R and 90 mM EtOH. To assess BBB integrity, levels of AQPs, MMPs, ZO-1, and laminin were determined by Western blot. Compared to control, OGD/R without EtOH significantly increased AQP-4, AQP-9, MMP-2, and MMP-9 levels, while decreasing ZO-1 and laminin levels. All EtOH concentration treatments (groups 3 through 5) significantly reduced the expressions of AQP-4, AQP-9, MMP-2, and MMP-9, compared to the OGD/R, non-alcohol treated slices. Furthermore, compared to the OGD/R without EtOH group, the 30 mM EtOH treatment significantly increased ZO-1 and laminin levels. In contrast, the 90 mM EtOH level neither enhanced the reduction in AQP and MMP levels nor increased ZO-1 or basal lamina expressions observed in the 30 mM treatment. In conclusion, at an optimal dose of 30 mM, EtOH improves the expressions of MMP-2, MMP-9, AQP-4, AQP-9, ZO-1, and basal laminin, previously altered by OGD/R. These effects may indicate a beneficial effect of EtOH on BBB integrity after stroke.